PERSEPSI GURU TERHADAP PENERAPAN SISTEM INFORMASI MANAJEMEN DI SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 3 PADANG - Vindi Agustiandra; Ahmad Sabandi (Universitas Negeri Padang, 2019)
This study aims to obtain information about Teacher's Perception of the Application of Academic Management Information Systems at Vocational High School (SMK) 3 Padang which is viewed from aspects: input, process, and output. This type of research is descriptive research. The population of this study were all teachers at SMK 3 Padang, amounting to 86 people. The instrument used to collect data is a questionnaire in the form of a Likert Scale with five alternative answers. The data that has been collected is then analyzed using the mean formula. The results showed that: (1) Input Activities in the Application of Academic Management Information Systems at SMK 3 Padang were in the good category with an average score of 4.09. (2) Process Activities in the Application of Academic Management Information Systems at SMK 3 Padang are in the good category with an average score of 4.11. 3) Output Activities in the Application of Academic Management Information Systems at SMK 3 Padang are in the good category with an average score of 4.07. Overall, the Application of Academic Management Information System at SMK 3 Padang is in a good category with an average score of 4.09.